The Impact of Social Entrepreneurship, Corporate Social Responsibilities, and Working Capital Management Practices on the Performance of Tourism Small–Medium Enterprises (SMEs) During COVID-19: Moderating Role of Employee Behavior - Li, Yuanyuan; Ahmad, Israr; Raza, Hassan; Sawangchai, Anusara; Ramirez-Asis, Edwin; Asnate-Salazar, Edwin (Frontiers in Psychology, 2022)
The failure or success of an enterprise depends upon its working capital management practices along with effective corporate social responsibilities (CSR) and social entrepreneurship. These factors ensure not only the soundness of financial indicators but also the profitability of an enterprise. Therefore, the objective of the study is to determine the impact of CSR, social entrepreneurship, and working capital management practices on the performance of small-medium enterprises (SMEs) of tourism sector. during the lockdown period in Malaysia. The goals also include the investigation of moderating role of employee behavior among the nexus of CSR, social entrepreneurship, working capital management practices, and performance of SMEs. The survey was performed to find out the practices adopted by the SMEs during corona days. A quantitative research method has been adopted to get data with convenient sampling technique, and PLS-SEM has been exploited to find out the significant nexus between CSR, social entrepreneurship, working capital management practices, and the performance of SMEs. The results indicate that CSR, social entrepreneurship, and working capital management practices have a positive association with the performance of SMEs in Malaysia. The results also indicate that employee behavior positively moderates among the nexus of CSR, social entrepreneurship, working capital management practices, and the performance of SMEs in Malaysia. Stock review strategies by the SMEs during the corona days also exhibit significant differences except for no stock review. Significant differences between the enterprises show a lack of adaptation of the financial indicators that determine enterprise soundness. The study not only provides guidelines for entrepreneurs of SMEs but also helps in maintaining standards for the evaluation of the enterprises.